How Implementation of Roadside Towing Application to Increase Interest in Using Car Towing Services? - Saputro, Rafi Eko; Afisa, Tiara; Hendratno, Dian Safira Putri; Reginawati, Temi; Hilal, Achmad; Ambarwati, Diana (Innovation Business Management and Accounting Journal, 2023)
A towing service business for car owners experiencing problems is a breath of fresh air so that road users no longer need to worry and can continue their journey in peace. Car towing services are a promising business in the current era, considering the large number of cars on the road. For this reason, the Roadside Towing website application allows users to easily order services for transporting broken down or damaged vehicles. This research aims to determine implementation, obstacles, and evaluation when experiencing obstacles in using the roadside towing application for towing service users. This research collects data using observation, experiment, and literature study. The informants in this research were 3 first users of the Roadside Towing website application in East Java and 2 founders. The Roadside Towing website application can technically be implemented for car towing service users by paying attention to the technical aspects of ordering services, obstacles, and evaluation using this application. It is hoped that future researchers can research with more significant number of informants and appropriate variables to increase their contribution in the field of operational management.